Study of Poly(vinyl alcohol)/Cyclodextrin Materials Obtained by Different Techniques - Patachia, Silvia; Croitoru, Catalin (Journal of Hydrogels, 2015)
Materials based on poly(vinyl alcohol) [PVA] and cyclodextrins [CDs] have been obtained by components mixing in aqueous solution and then, by applying two different techniques of PVA crosslinking: chemical crosslinking with glutaraldehyde in gaseous phase and physical crosslinking (repeated freezing-thawing cycles), aiming the obtaining of materials with different properties and potential applications. Three cyclodextrin derivatives such as beta-cyclodextrin, methyl beta-cyclodextrin and hydroxypropyl beta-cyclodextrin have been used. The obtained materials have been characterized from different points of view: compositional stability at their contact with water (CDs release), materials water sensitivity (swelling capacity), thermal stability and molecular interaction (FTIR absorption).
Keywords: Poly(vinyl alcohol); Cyclodextrins; Crosslinking; Cryogels.